2021
DOI: 10.1111/1462-2920.15382
|View full text |Cite
|
Sign up to set email alerts
|

Induction of antibiotic specialized metabolism by co‐culturing in a collection of phyllosphere bacteria

Abstract: A diverse set of bacteria live on the above-ground parts of plants, composing the phyllosphere, and play important roles for plant health. Phyllosphere microbial communities assemble in a predictable manner and diverge from communities colonizing other plant organs or the soil. However, how these communities differ functionally remains obscure. We assembled a collection of 258 bacterial isolates representative of the most abundant taxa of the phyllosphere of Arabidopsis and a shared soil inoculum. We screened … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 115 publications
(175 reference statements)
0
10
0
Order By: Relevance
“…In the frame of several efforts to maximally isolate the cultivable bacterial community of a topsoil sample of the Aelmoeseneie forest, more than 5000 isolates have been examined thus far ( [36] and data from the present study). These isolates have all been dereplicated by MALDI-TOF MS using the SPeDE algorithm [45] to remove redundant isolates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the frame of several efforts to maximally isolate the cultivable bacterial community of a topsoil sample of the Aelmoeseneie forest, more than 5000 isolates have been examined thus far ( [36] and data from the present study). These isolates have all been dereplicated by MALDI-TOF MS using the SPeDE algorithm [45] to remove redundant isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Sixty seven forest soil isolates were selected after matrix-assisted laser desorption/ ionization time-of-flight mass spectrometry (MALDI-TOF MS) dereplication analyses performed in the present and previous studies [36] (Table 1). Of these isolates, 23 were picked from 1/100 diluted nutrient broth solidified with Gelzan CM (DNG), 24 from B. cepacia complex enrichment medium (BCEM), 17 from 1/10 diluted Pseudomonas cepacia azaleic acid tryptamine medium (PCAT) and 3 from modified Pikovskaya medium.…”
Section: Isolation Of Paraburkholderia Isolatesmentioning
confidence: 99%
“…For instance, in a recent study, Qi et al . analysed about 3400 forest soil isolates which were dereplicated into 258 MALDI-TOF mass spectrometry-defined independent strains [10]. While subsequent publications reported three novel Pedobacter and six novel Paenibacillus species [11, 12], near full length 16S rRNA sequence analyses revealed dozens of additional novel species and genera in this collection [10].…”
Section: Full-textmentioning
confidence: 99%
“…analysed about 3400 forest soil isolates which were dereplicated into 258 MALDI-TOF mass spectrometry-defined independent strains [10]. While subsequent publications reported three novel Pedobacter and six novel Paenibacillus species [11, 12], near full length 16S rRNA sequence analyses revealed dozens of additional novel species and genera in this collection [10]. A major reason why only nine novel species from this collection have been formally named so far is the frequently encountered insistence of journal editors that authors provide ‘polyphasic’ taxonomic descriptions that are as comprehensive as possible and that include multiple types of chemotaxonomic data, reflecting recommendations from a decade ago [13].…”
Section: Full-textmentioning
confidence: 99%
“…However, multiple significant differences in the predicted functions of the core and SA-selected communities suggests that SA signaling results in many gained functions, whether beneficial or detrimental to the host plant. Previous research has demonstrated that the bacterial phyllosphere microbiome has the capacity to both produce and metabolize antibiotics, but that the magnitude is dependent on extrinsic cues, including biotic stress responses ( Chen et al, 2018 ; Qi et al, 2021 ; Yan et al, 2021 ). The research presented here predicts that SA signaling selects for bacteria associated with the biosynthesis of antibiotics.…”
Section: Discussionmentioning
confidence: 99%